Pengujian Black Box pada Aplikasi Sistem Kasir Berbasis Website Menggunakan Teknik Equivalence Partitions - Aziz, Irfan Abdul; Setiawan, Bagas; Khanh, Rashad; Nurdiyansyah, Guruh; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Nowadays, computers have an important role in human life. Because computers really help humans in carrying out tasks through the applications and features available according to human needs. Most of the people who have a business doing all their activities are more computerized on a regular basis for reasons of time, less risk and faster decisions than without a computer. For this reason, the purpose of this study is to produce a cashier information system that can conduct deposit sales and produce multiple transaction reports. This Cashier System was designed using php and MySQL programming languages with XAMPP software.